Lifetime Physical Fitness and Wellness: A Personalized Program, 15th Edition - Wener Hoeger (Cengage Learning, 2018)
LIFETIME PHYSICAL FITNESS AND WELLNESS, 15th Edition, provides the information, tools and guidelines students need to create and follow a lifelong physical fitness and wellness program. Led by Werner W.K. Hoeger, the authors help readers evaluate current behaviors, identify negative habits and adopt healthy practices for the long term--teaching them how to take control of their lifestyles. Personalized information helps students relate content to their own lives, while hands-on activities enable them to immediately apply what they learn through self-review and other applications. The capstone chapter of exercise programming, Chapter 9 gives students confidence to write their own exercise programs.